COMPUTATIONAL STUDY ON THE ACTIVITY AND SELECTIVITY OF CARBON DIOXIDE REDUCTION REACTION TO CARBON MONOXIDE AND FORMIC ACID ON NICKEL COBALT PHOSPHATE SURFACES DOPED WITH TRANSITION METALS - Primipara, Raka
The electrochemical reduction of CO2 is one approach to reducing greenhouse gas emissions in the atmosphere while simultaneously producing chemicals that are more useful than CO2 itself. One of the main challenges in developing such electrocatalysis systems is finding catalysts that are selective and operate at low overpotentials. Single-atom Ni-based catalysts have shown promising potential, but several issues remain, such as the catalyst's properties not being fully understood and the presence of relatively high overpotentials In this study, we explore the activity and selectivity of the CO2 reduction reaction (CO2RR) to CO and HCOOH on pure and transition metal-doped NiCoPO(100) surfaces using density functional theory (DFT) calculations. Our analysis reveals that transition metal doping (Mn, Fe, and Cu) through substitutional defects influences the limiting potentials of the CO2RR process. While the activity toward CO formation remains largely unchanged across doped and undoped NiCoPO(100) surfaces, the introduction of these dopants significantly enhances the production of HCOOH. Notably, the limiting potential for HCOOH formation is generally higher than for CO, indicating a preference for CO production in most cases. However, Mn doping uniquely shifts this preference, making HCOOH formation more favorable. Additionally, Mn doping effectively reduces the impact of the parasitic hydrogen evolution reaction (HER), aligning the energetic pathway closer to HCOOH production. These findings suggest that Mn-doped NiCoPO(100) surfaces are promising candidates for optimizing CO2RR efficiency and selectivity, contributing to the development of more effective catalysts for sustainable carbon conversion technologies. Keywords: Carbon Dioxide Reduction Reaction (CO2RR), Nickel Cobalt Phosphate (NiCoPO(100)), Transition Metal Doping, Density Functional Theory (DFT), CO formation, HCOOH formation